O tempo, o caminho e a experiência do coordenador pedagógico da creche: as rotinas e os saberes que articulam, formam e transformam suas práticas educacionais - Sula, Margarete Cazzolato (2016)
This study had the main objective to analyze the professional knowledge of the pedagogical coordinator who works in day care centers of the municipal Santo André, from their pedagogical monitoring routines and their coordinating actions, forming and transforming educational practices. The research problem originated from a reflective dialogue between the professional experience, as a Coordinator of Educational Services, with the theoretica l frameworks of the course - Master Professional "Training of Trainers" at PUC-SP. The research showed as an ethnographic study of a qualitative nature. In the theoretical foundation, is approached through a triad, the issue of teaching knowledge in the contemporary academic context; functions, routines and underlying challenges for the work of the pedagogical coordinator and the day care context. It also presented an overview of early childhood education, contextualizing the legal frameworks and the conception of the child, seen as an individual of rights and producer of culture. Questionnaires and interviews were used as data collection instruments. The questionnaire data supported a characterization of the group, highlighting their school life and career path and comparing problems, challenges, charms and disillusions function. Afterwards, four coordinators were interviewed, using a semi-structured interview guide. The findings were organized in the light of seven categories, inspired by theoretical frameworks of Almeida, Placco, Souza, Tardif, Vasconcellos, among others, dialoguing with the emerging knowledge of the professionals’ speeches. The survey results indicated that the network coordinators group shows itself in a continuous process of constitution. The coordinators interviewed have a pedagogical monitoring routine, which, although it shows planned, it is still fragile and crossed by everyday occurrences. It was evident the difficulty in organizing and strengthening the training actions, curtailed by the continuing challenges of the order, given the continuous turnover of professionals who step into nursery. The coordinators see themselves as restless professionals, in constant learning process, formation and transformation. The findings reveal involvement in coordinating actions to mobilize the different groups for the implementation of the political pedagogical project. Interpersonal relationships highlighted among the main tensions and concerns experienced by the group. The coordinators, who mobilize and provide knowledge for conflict mediation, understand the importance of building a collective work, in which knowing how to look, to listen and to speak reveal fundamental knowledge. It also showed that the coordinators mobilize knowledge of a different nature to articulate the collective, to form them to the challenges of the present time, combined the needs of unlinking the nursery of welfare practices to transform the educational routines. The survey also revealed different experiential knowledge, built up over time and the way experienced during the function, among them the knowledge of historicity, fundamental to the constitution of the childcare professionals identity, both for understanding the specifics of the service, and to aware new professionals and promote public training policies